Surface modification of poly(propylene) fabric with graphene oxide‐based silver nanoparticles for antibacterial applications. Issue 45 (23rd September 2022) - Dat, Nguyen Minh; Huong, Le Minh; Tinh, Ninh Thi; Linh, Nguyen Thi Thuy; Hai, Nguyen Duy; Viet, Nguyen Duc; Thinh, Doan Ba; Cong, Che Quang; Dat, Nguyen Tien; Phong, Mai Thanh; Hieu, Nguyen Huu
Abstract: Herein, poly(propylene) (PP) was hydrophilized with oxidating agents and solvents, followed by dip‐coating with silver nanoparticles anchored GO sheets (Ag@GO) prepared by the in‐situ method as reported in our previous study to obtain silver@graphene oxide‐coated poly(propylene) (Ag@GO/PP). The impact of the modifying agents, dipping times, and coating concentrations on the antibacterial activities were studied accordingly via the inhibition zone method. The fabrics were re‐hydrophobized with the reduction of Ag@GO and the functionalization with stearic acid (SA) to form silver@reduced graphene oxide‐coated poly(propylene) (Ag@rGO/PP) and silver@graphene oxide/SA‐coated poly(propylene) (Ag@rGO‐SA/PP), respectively. Characterization of pretreated and modified PP samples was carried out by various modern analysis methods. Simultaneously, the cytotoxicity of the active layers, the release of Ag + ions, and durability after washing were also investigated. The obtained results representing PP fabrics pretreated with HNO3 /isopropanol and dipped in Ag@GO concentration of 2 g/L four times prove a sufficient approach for improving hydrophilization and bio‐compatibility for the PP samples. The fabrics greatly show an impressive interaction with precursors, mostly high antibacterial activity even after four washing cycles via appropriate releasing of Ag + to ensure the safety in usage. They further suggest that the prepared fabrics could be utilized for actual application as a face mask. Abstract :